Let x be the number of pints of 65% pure fruit juice drink and y the number of pints of the 90% pure fruit juice drink
Then we have:
![\begin{gathered} x+y=90 \\ (0.65x+0.9y)/(90)=0.7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9wxyqwhvcrpw0769k5xhc3rr9mzp3f120o.png)
From the first equation, we have y = 90 - x.
Replacing y in the second equation, we got:
![\begin{gathered} (0.65x+0.9(90-x))/(90)=0.7 \\ 0.65x+0.9(90-x)=63 \\ 0.65x+81-0.9x=63 \\ 0.25x=18 \\ x=72 \\ \therefore y=90-72=18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o47l651v94lo8wxx7t1p5a3a5ga4it78c9.png)
Answer:
First fruit drink: 72 pints
Second fruit drink: 18 pints